Expressive Acts in Wild Child Movie: Pragmatics Study - Nodea Dwi Suhatati; Ervina CM Simatupang (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The purposes of this study are to identify the types and functions of expressive acts in a pragmatic study. This research used descriptive qualitative as the method in providing data analysis. The data were collected from the Wild Child movie. The instruments used in this research are the utterances of the characters. In this research, the data has been analyzed by using the theory of the expressive act by Searle (1976) to answer the research question. According to the findings of this study, there are five different types of expressive acts which are uttered 36 times such as, thanking, praising, greeting, asking for an apology, and congratulating. The data consist of 10 data of apologizing (27.7%), 7 data of praising (19.5%), 7 data of thanking (19.5%), 1 data of congratulating (2.7%), and 11 data of greeting (30.5%). The type of expressive act that is dominant is greeting, which is 30.5% of the data (11 data). The functions of expressive acts that are found in Wild Child movie are 19.5% expressing thanking (7 data), 19.5% expressing praising (7 data), 30.5% expressing greeting (11 data), 27.7% expressing apologizing (10 data), and 2.7% expressing congratulating (1 data). The most dominant function of the expressive act in Wild Child movie is the function of greeting with 11 data (30.5%).